Low-pressure injection molding heat-conducting insulating compound
By using thermal filler composites of various particle sizes in low-pressure injection molded thermal hot melt adhesive materials to blend with thermoplastic polymers and adding viscosity reducing agents, the problem of material settlement and cracking during use is solved. It achieves both thermal conductivity, insulation and toughness, and is suitable for packaging of precision electronic products.
Patent Information
- Application Number
- CN202411308564.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-07
AI Technical Summary
The existing low-pressure injection-molded thermally conductive hot-melt adhesive materials are prone to settle in a molten state, affecting their uniformity and stability. At the same time, it is difficult to take into account both thermal conductivity and insulation, and cracking is prone to occur during use.
The thermal filler composite with particle sizes of 20-30μm, 10-20μm, 4-10μm and 0.4-4μm are blended with thermoplastic polymers, and a viscosity reducing agent is added to control viscosity and toughness to ensure that the thermal filler does not be in a molten state. Settling and no cracking occurs during use.
It achieves the balance of thermal conductivity, insulation, toughness and low-pressure injection moldability. The product is stable in the molten state, does not settle, and is not easy to crack during use. It is suitable for packaging of precision electronic products.
Smart Images

Figure CN119391179A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of melt blending and modification of thermoplastic polymers, in particular to a low-pressure injection-molded heat-conducting and insulating composite. Background Art
[0002] In recent years, benefiting from technological progress, increased consumer demand and the development of emerging markets, the development of the electronics industry has shown a positive trend, and at the same time has promoted the development of corresponding auxiliary materials. Among many auxiliary materials, encapsulation glue is a very important one, which is used to protect the integrated circuits in electronic products from interference from external environmental factors, and its demand is quite considerable.
[0003] At present, the development trend of electronic products is mainly focused on high integration, miniaturization, precision and high power. The heat generated during use increases sharply, and thermal failure has become the primary factor affecting the performance and life of electronic products. Therefore, for electronic product packaging glue, it is necessary not only to achieve the bonding and packaging function, but also to play a good heat dissipation role, so as to more effectively protect the usability of electronic products and extend their life.
[0004] In this field, there are patents or reports on potting compounds based on polymers such as silicone and epoxy resin. Most of them add thermal conductive fillers, curing agents and other additives to liquid polymers, then encapsulate them on electronic components by casting, and finally cure them by cross-linking to achieve the encapsulation thermal conductivity effect.
[0005] In order to meet the packaging requirements of certain precision electronic products, there are currently patents or reports based on thermally conductive thermoplastic resins. Patents CN117004217A, CN117903531A, CN114507379B, etc. disclose thermally conductive thermoplastic resins. The polymers used are thermoplastic nylon plastics, polyolefins, polyvinylidene fluoride (PVDF), etc., which generally have a large melt viscosity and require a large pressure for injection molding.
[0006] In order to meet the protection needs of increasingly miniaturized and sophisticated electronic products, low-pressure injection molding has more application prospects. It can not only meet more complex molding needs, but also the lower injection pressure will not cause damage to electronic products.
[0007] In order to meet the needs of low-pressure injection molding, the viscosity of the thermal conductive product should not be high. To this end, patent CN113403020A discloses a thermally conductive PA insulating hot melt adhesive, which includes polyamide (PA), tackifying resin, synthetic wax, thermally conductive filler, plasticizer, etc., wherein the polyamide resin is polyamide 6 (PA6) nylon plastic. In order to reduce the melt viscosity of the thermal conductive product so that it can be molded by low-pressure injection molding, the patent adds a large amount of small molecule tackifying resin, synthetic wax, and plasticizer. The ratio of the total amount of PA6 nylon plastic to the small molecule additive is 1:1-1:3. Relevant researchers have found that when the mass ratio of thermoplastic resin to small molecule additive is less than 2.5:1, or the content of thermoplastic resin is less than 26wt%, the resulting product has poor toughness and there is a risk of cracking during use.
[0008] In order to obtain a thermoplastic thermally conductive material with good toughness and low-pressure injection molding, some people currently prepare thermally conductive hot melt adhesives by mixing thermally conductive fillers into hot melt adhesive resins with low melt viscosity. Patent CN109416953A discloses a conductive hot melt adhesive or molding composition, which includes a PA hot melt adhesive polymer, and graphite and metal thermally conductive fillers. Patent CN109370479B discloses a method for preparing a thermally conductive hot melt adhesive, which includes a thermally conductive hot melt adhesive, and the thermally conductive hot melt adhesive includes ethylene-vinyl acetate (EVA) copolymer, terpene resin, graphene thermally conductive filler and other additives. Patent U2016 / 0032166A1 discloses a thermally conductive hot melt adhesive and a method for preparing the same, which includes a thermally conductive hot melt adhesive, and the thermally conductive hot melt adhesive includes polyethylene terephthalate (PET), EVA, and zinc oxide (ZnO) and aluminum (Al) powder thermally conductive fillers. Patent CN118103474A discloses a hot melt adhesive composition, which contains PA and expanded graphite thermal conductive filler. The low-pressure injection molding thermal conductive hot melt adhesive material mentioned in the above patent is mixed with conductive thermal conductive filler during the preparation process, and the insulation of the product is not easy to ensure.
[0009] From the perspective of application safety, low-pressure injection molding thermally conductive hot melt adhesive with insulation has more application prospects in the field of electronic product packaging. Patent CN107667156A discloses a hot melt adhesive with high thermal conductivity and low pressure molding, including polymer hot melt adhesive, spherical alumina (Al2O3), and plate-shaped Al2O3 thermal conductive filler, wherein the proportion of Al2O3 filler is 40-70wt%, and the thermal conductivity of the product is 0.44-1.48W / m·K. Patent CN103555262B discloses a thermally conductive hot melt adhesive. The thermally conductive hot melt adhesive includes PA, titanium dioxide (TiO2), zirconium silicate (ZrSiO4), Al2O3 and other thermally conductive fillers. Among them, the proportion of thermally conductive filler is 50-70wt%, and the thermal conductivity of the product is 0.42-0.79W / m·K. Patent CN101935503B discloses a thermally conductive ethylene-vinyl acetate copolymer hot melt adhesive. The thermally conductive hot melt adhesive includes EVA, Al2O3, ZnO, magnesium oxide (MgO) thermally conductive fillers, etc. In the embodiment, the thermally conductive filler accounts for about 59.5wt%, and the thermal conductivity of the product is 0.72-1.02W / m·K.
[0010] The low-pressure injection molding insulating heat-conducting insulating hot melt adhesive material mentioned in the above patent has a density greater than 3g / cm 3 Thermally conductive fillers (such as TiO2, ZrSiO4, Al2O3, etc.) account for the majority. Relevant researchers have found that when the density is greater than 3g / cm 3 The filler content in the product is greater than 20wt%, or the density is less than 3g / cm 3 Filler with density greater than 3g / cm 3 When the mass ratio of the filler is less than 1.5:1, the hot melt adhesive product will settle in the molten state, thus affecting its uniformity and stability.
[0011] In addition, the alumina thermal conductive filler used in the hot melt adhesive with high thermal conductivity and low pressure molding disclosed in patent CN107667156A contains Al2O3 spherical particle fillers with a size of 35-55μm. Relevant researchers have found that in common melt blending processes, such as twin-screw extrusion, fillers with a size greater than 30μm will be crushed, thereby reducing the performance stability of the product.
[0012] Based on the above background, it is of certain significance to develop a composite material that can take into account thermal conductivity, low-pressure injection moldability, insulation, uniformity and stability at the same time, especially for the packaging of micro high-precision electronic equipment. If inorganic non-metallic powders with small size, low density, high thermal conductivity and insulation can be used as the main filler and blended with polymers with low bulk viscosity, it is expected to obtain a non-sedimentation, relatively stable low-pressure injection-molded thermal conductive insulating composite. If a small amount of oligomers can be mixed into the system in a certain proportion, it is expected to reduce the viscosity of the system and meet the requirements of low-pressure injection molding while maintaining thermal conductivity, insulation and stability, and at the same time meet the toughness requirements of the product, and no cracking will occur during use. Summary of the invention
[0013] In order to overcome the above-mentioned defects of the prior art, the object of the present invention is to provide a low-pressure injection-molded thermally conductive insulating composite.
[0014] The low-pressure injection-molded thermally conductive insulating composite of the present invention not only has relatively excellent thermal conductivity and insulation, but also has low viscosity, and can be injection-molded at a relatively low pressure in a molten state. In addition, the thermally conductive composite can be relatively stable in a molten state, does not settle, and does not crack during use.
[0015] In order to achieve the purpose of the present invention, the technical solution adopted is:
[0016] A low-pressure injection-molded thermally conductive insulating composite, calculated by mass, comprises the following components:
[0017] 30-55 parts of thermoplastic polymer;
[0018] 40-65 parts of thermal conductive filler compound;
[0019] 5-15 parts of viscosity reducer;
[0020] The thermally conductive filler compound is a compound of the following components:
[0021] A first thermally conductive filler having a particle size of 20-30 μm;
[0022] A second thermally conductive filler having a particle size of 10-20 μm;
[0023] A third thermally conductive filler having a particle size of 4-10 μm;
[0024] A fourth thermally conductive filler having a particle size of 0.4-4 μm;
[0025] The mass ratio of the first thermally conductive filler to the second thermally conductive filler is 1:1-2:1;
[0026] The mass ratio of the second thermally conductive filler to the third thermally conductive filler is 1:1-2:1;
[0027] The mass fraction ratio of the sum of the mass fractions of the first thermally conductive filler, the second thermally conductive filler and the third thermally conductive filler to the mass fraction of the fourth thermally conductive filler is 1.5:1-5:1.
[0028] The first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler is III A Group IV nitrides A Group VIII oxides, Group I B Any one or more oxides of group elements;
[0029] The fourth thermally conductive filler is a non-VIII group transition element oxide, II A Group III oxides A Group III oxides A Group IV Hydroxides A Group IV oxides A Group IV nitrides A Any one or more of carbides of Group VIII elements or alkaline silicates of transition metal elements other than Group VIII;
[0030] The total amount of the thermoplastic polymer, the thermal conductive filler compound and the viscosity reducer is 100 parts.
[0031] The components are mixed and extruded to obtain a low-pressure injection-molded thermally conductive insulating composite.
[0032] The first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler has a density less than 3 g / cm 3 Sheet insulation filler.
[0033] The first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler has a density less than 3 g / cm 3 Flake boron nitride (BN), preferably with a density of 2.3 g / cm 3 It has excellent thermal conductivity and insulation properties. A small amount of addition can significantly improve the thermal conductivity of the product and prevent the product from settling in the molten state, making it a relatively good choice.
[0034] The fourth thermally conductive filler has a density less than 4 g / cm 3 Granular insulating filler.
[0035] The fourth thermally conductive filler has a density less than 4 g / cm 3 Granular Al2O3, preferably with a density of 3.3 g / cm 3 .
[0036] The purpose of adding the fourth thermally conductive filler is to fill the gaps in the thermally conductive frame formed by the lamellar first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler in the product, to form a more complete thermally conductive path, and to further improve the thermal conductivity of the product.
[0037] The total weight of the insulating composite is 100 parts, and the sum of the weight parts of the thermoplastic polymer and the viscosity reducer is 35-60 parts;
[0038] The ratio of the mass fraction of the thermoplastic polymer to the mass fraction of the viscosity reducer is not less than 2.5-3:1.
[0039] The ratio of the mass fraction of the thermoplastic polymer to the mass fraction of the viscosity reducer is not less than 3:1.
[0040] The inventors have found through a large number of experiments that this can ensure that the product has good toughness and will not crack during use. In addition, adding a viscosity reducer into the system at an appropriate mass fraction can not only significantly reduce the viscosity, but also keep the thermal conductivity of the product unchanged.
[0041] The mass fraction ratio of the first thermally conductive filler to the second thermally conductive filler is controlled within the range of 1:1-2:1, and the mass fraction ratio of the second thermally conductive filler to the third thermally conductive filler is controlled within the range of 1:1-2:1, and the mass fraction ratio of the sum of the mass fractions of the first thermally conductive filler, the second thermally conductive filler and the third thermally conductive filler to the fourth thermally conductive filler is controlled within the range of 1.5:1-5:1. When the above points are met at the same time, it can be ensured that the product will not settle in the molten state and has good stability, and the thermal conductivity of the product can be maximized while maintaining the viscosity.
[0042] The thermoplastic polymer is any one or more of a carbon-based linear polymer obtained by addition polymerization or copolymerization of olefin monomers through carbon-carbon double bonds (-C=C-), a carbon-based linear polymer whose main chain contains an amide bond (-CO-NH-) obtained by stepwise polycondensation or ring-opening polymerization, a carbon-based linear polymer whose main chain contains an ester group (-COO-) obtained by stepwise polycondensation or ring-opening polymerization, or a carbon-based linear polymer whose main chain contains an urethane group (-NH-COO-), and a carbon-based linear polymer obtained by stepwise addition polymerization using diisocyanates and diols.
[0043] The carbon-based linear polymer obtained by addition polymerization or copolymerization of olefin monomers through carbon-carbon double bonds (-C=C-) is any one or more of polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), polymethyl methacrylate (PMMA), ethylene-propylene rubber (EPR), ethylene-vinyl acetate copolymer (EVA), ethylene-octene copolymer, ethylene-butene copolymer, ethylene-ethyl acrylate copolymer (EEA), ethylene-propylene rubber (TEPR), a triblock copolymer (SBS) with styrene and butadiene as monomers, acrylonitrile-butadiene-styrene block copolymer (ABS) or butyl rubber (BR).
[0044] The carbon-based linear polymer having an amide bond (-CO-NH-) in the main chain obtained by stepwise polycondensation or ring-opening polymerization is any one or more of PA6, polyamide 66 (PA66), polyamide 610 (PA610), polyamide 1010 (PA1010), and dimer acid type polyamide.
[0045] The carbon-based linear polymer whose main chain contains an ester group (-COO-) obtained by stepwise polycondensation or ring-opening polymerization is any one or more of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene isophthalate, polyethylene isophthalate, butylene adipate-butylene terephthalate copolymer (PBAT), polyethylene furandicarboxylate, polybutylene furandicarboxylate, polylactic acid (PLA), and lactic acid-glycolic acid copolymer (PLGA).
[0046] The thermoplastic polymer is a dimer acid type polyamide, which is obtained from the following monomers by stepwise polycondensation or ring-opening polymerization:
[0047] (1) Dimer acid with a molecular weight of 100-10000;.
[0048] (2) diamines containing 2 to 20 carbon atoms in the main chain;
[0049] (3) dibasic acids with a main chain containing 4 to 20 carbon atoms;
[0050] (4) Polyetheramine with a molecular weight of 100-10000.
[0051] The molecular weight of the dimer acid is in the range of 100-2000.
[0052] The diamine is any one or more of ethylenediamine, hexamethylenediamine, octanediamine, decanediamine, dodecanediamine, octadecanediamine or 2,2,4-trimethylhexamethylenediamine.
[0053] The dibasic acid may be any one or more of succinic acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, octadecane dioic acid, terephthalic acid, isophthalic acid, and furandicarboxylic acid.
[0054] The molecular weight of the polyetheramine is in the range of 100-4000.
[0055] The viscosity reducing agent is a carbon-based linear oligomer with a molecular weight not exceeding 2,000.
[0056] The beneficial effects of the present invention are:
[0057] It not only has good thermal conductivity, insulation, toughness, and low-pressure injection moldability, but also during the preparation process, the filler can maintain its morphology and will not break, and the product performance is relatively stable.
[0058] In addition, the product has a low viscosity in the molten state, does not settle, and does not crack during use, and can be very well applied to the packaging of electronic products with relatively precise structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a schematic diagram of the product of Example 1.
[0060] Figure 2 This is a schematic diagram of the product of Comparative Example 2.
[0061] Figure 3 This is a processing schematic diagram of Example 1. DETAILED DESCRIPTION
[0062] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following structure, the description of the known structure and technology is omitted to avoid unnecessary confusion of the concept of the present invention.
[0063] In the description of the present invention, it should be noted that the terms “first” and “second” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0064] The present invention is fully described below in conjunction with specific embodiments:
[0065] The ZSB-180-II mentioned in the examples is a dimer acid polyamide product produced by Shanghai Liri Chemical New Materials Co., Ltd., with a brand name of ZSB-180-II. Its softening point is 180°C, its melt viscosity is 3200 cP at 210°C, its thermal conductivity is 0.25 W / m·K, and its volume resistivity is about 1.10×10 12 Ω·cm.
[0066] The BN-S, BN-N, and BN-C mentioned in the examples are flaky hexagonal boron nitride products with particle sizes of about 20-30 μm, 10-20 μm, and 5-10 μm produced by Yingkou Liaobin Fine Chemical Co., Ltd., and the brands are BN-S, BN-N, and BN-C, respectively.
[0067] The NSM-2S mentioned in the examples is a granular alumina product with an average particle size of about 1.7 μm produced by Ya'an Baitu High-tech Materials Co., Ltd., with a brand name of NSM-2S.
[0068] The BAK-40 mentioned in the examples is a spherical alumina product with an average particle size of about 40 μm produced by Ya'an Baitu High-tech Materials Co., Ltd., with a brand name of BAK-40.
[0069] The TW-F3041 mentioned in the examples is a carbon-based linear oligomer produced by Jiangsu Tianwen New Material Technology Co., Ltd., with the brand name TW-F3041.
[0070] The twin-screw extruder mentioned in the examples is a twin-screw extruder produced by Nanjing Ruiya Polymer Equipment Co., Ltd., model TSE-35A.
[0071] The melting sedimentation mentioned in the embodiment is tested by the following method: the obtained product is placed in a cylindrical glass container with a bottom inner diameter of 5 cm and a height of 10 cm, and melted at 210°C. The depth of the melt in the container after melting is controlled to be 6 cm. After standing for 8 hours, it is placed at room temperature for 24 hours to solidify the product. After that, the glass container is broken, and cylindrical samples of 1 cm at the top and 1 cm at the bottom of the product are cut, and the density is measured respectively, and compared. If the density of the bottom sample is more than 10% greater than the density of the top sample, it is determined to be melting sedimentation, otherwise, it is determined to be no melting sedimentation.
[0072] The melt viscosity at 210° C. mentioned in the examples is tested according to HG / T 3660-1999.
[0073] The thermal conductivity mentioned in the examples is tested according to ASTM-D5470-12.
[0074] The volume resistivity mentioned in the examples is tested in accordance with GB / T 31838.2-2019.
[0075] The elongation at break mentioned in the examples is tested in accordance with GB / T 528-2009.
[0076] The specific implementation examples are shown in Tables 1 and 2. According to the mass ratios shown in Tables 1 and 2, ZSB-180-II, BN-S, BN-N, BN-C, NSM-2S and TW-F3041 raw materials are mixed evenly, and then melt-blended, extruded and granulated using a twin-screw extruder to obtain an insulating, thermally conductive, insulating composite product that can be injection molded at low pressure.
[0077] Table 1 Example Raw Material Mass Ratio
[0078]
[0079] Table 2 Comparative Example Raw Material Mass Ratio
[0080]
[0081] Table 2
[0082]
[0083]
[0084] The performance of the products prepared in the embodiment and the comparative example was characterized, and the results shown in Table 3 and Table 4 were obtained.
[0085] Table 3 Example product performance
[0086] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Melt Sedimentation no no no no no no no no 210℃ Melt viscosity / cP 7000 9200 12200 14800 12900 6800 7000 5100 <![CDATA[Thermal conductivity / W·(m·K) -1 > 1.52 2.36 2.79 2.98 1.49 1.12 1.14 1.01 Volume resistivity / Ω·cm <![CDATA[1.10×10 11 ]]> <![CDATA[7.71×10 10 ]]> <![CDATA[4.67×10 10 ]]> <![CDATA[1.94×10 10 ]]> <![CDATA[9.94×10 10 ]]> <![CDATA[1.92×10 11 ]]> <![CDATA[2.36×10 11 ]]> <![CDATA[5.65×10 11 ]]> Elongation at break / % 35 30 25 20 37 33 36 39
[0087] Table 4 Comparative Example Product Performance
[0088]
[0089] Table 4
[0090]
[0091] The products obtained in Example 1 and Comparative Example 2 were calcined at 560° C. for 2 h and the remaining products were observed using a scanning electron microscope. The images obtained were as follows: Figure 1 and Figure 2 As shown, the red arrows point to the NSM-2S and BAK-40 fillers in the product, respectively.
[0092] The product obtained in Example 1 was molded into a product such as Figure 3 shown.
[0093] contrast Figure 1 and Figure 2It can be seen that compared with the larger Al2O3 filler (about 40μm), the smaller Al2O3 filler (1.7μm) can better maintain its morphology and size during the processing. This shows that the alumina filler is not easy to break during the preparation process of the product, which can give the product more stable performance.
[0094] Depend on Figure 3 It can be seen that the product obtained in Example 1 can be well processed by low-pressure injection molding, and the morphology of the obtained product can be kept good without cracking.
[0095] From the results in Table 3 and Table 4, we can see that:
[0096] By comparing Comparative Example 1 with the embodiment, it can be found that after the compound thermal conductive filler and the viscosity reducer are blended with the thermoplastic polymer in the proportion described in the invention, the thermal conductivity of the product can be significantly improved, the melt viscosity, toughness and volume resistivity can be controlled within a relatively ideal range, and the product does not settle in the molten state and is relatively stable.
[0097] Comparing Comparative Example 2 with Example 1, it can be found that if a smaller Al2O3 filler is used, not only can the filler be better kept intact during the product preparation process, but the thermal conductivity of the product can also be improved, the viscosity is lower, and it is easier to meet the requirements of low-pressure injection molding.
[0098] Comparing Comparative Example 3 with Example 1, it can be found that when the content of the composite thermally conductive filler is higher than 40 wt %, the thermal conductivity of the product can be significantly improved.
[0099] Comparing Comparative Examples 4 and 5 with Example 1, it can be found that when the total mass fraction of the thermoplastic polymer and the viscosity reducer is higher than 35wt%, and the mass ratio of the two is higher than 2.5:1, the elongation at break of the product can be higher than 10%, and the product can have better toughness and is less likely to crack.
[0100] That is, based on 100 parts of the total amount of the insulating composite, the sum of the mass fractions of the thermoplastic polymer and the viscosity reducer is 35-60 parts, and the mass fraction of the thermoplastic polymer is not less than three times the mass fraction of the viscosity reducer.
[0101] Comparing Comparative Example 6 with Example 1, it can be found that the addition of the viscosity reducer can not only significantly reduce the viscosity of the product, but also the thermal conductivity of the product will not be greatly affected.
[0102] Comparing Comparative Examples 7 to 18 with the embodiment, it can be found that when the first thermally conductive filler, the second thermally conductive filler and the third thermally conductive filler of the flaky thermally conductive filler meet the mass ratio characteristics described in the content of the invention, the thermal conductivity of the product can be significantly improved and the melt viscosity of the product can be better controlled.
[0103] Comparing Comparative Examples 19 and 20 with Example 1, it can be found that when the density is less than 3 g / cm 3 Fillers (first thermally conductive filler, second thermally conductive filler, third thermally conductive filler) with a density greater than 3g / cm 3 The filler (the fourth thermally conductive filler) has a mass ratio greater than 1.5:1 and a density greater than 3g / cm 3 When the filler content in the product is less than 15wt%, it is better to ensure that the product will not settle in the molten state and has excellent uniformity and stability.
[0104] Comparing Comparative Example 21 with Example 1, it can be found that the addition of the granular fourth thermally conductive filler can effectively improve the thermal conductivity of the product while maintaining the viscosity.
[0105] The basic principles and main features of the invention and the advantages of the invention are shown and described above.
[0106] Those skilled in the art should understand that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A low-pressure injection-molded thermally conductive insulating composite, calculated by mass, characterized in that: The components include: 30-55 parts of thermoplastic polymer; 40-65 parts of thermal conductive filler compound; 5-15 parts of viscosity reducer; The thermally conductive filler compound is a compound of the following components: A first thermally conductive filler having a particle size of 20-30 μm; A second thermally conductive filler having a particle size of 10-20 μm; A third thermally conductive filler having a particle size of 4-10 μm; A fourth thermally conductive filler having a particle size of 0.4-4 μm; The mass ratio of the first thermally conductive filler to the second thermally conductive filler is 1:1-2:1; The mass ratio of the second thermally conductive filler to the third thermally conductive filler is 1:1-2:1; The mass fraction ratio of the sum of the mass fractions of the first thermally conductive filler, the second thermally conductive filler and the third thermally conductive filler to the mass fraction of the fourth thermally conductive filler is 1.5:1-5:1; The first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler is III A Group IV nitrides A Group VIII oxides, Group I B Any one or more oxides of group elements; The fourth thermally conductive filler is a non-VIII group transition element oxide, II A Group III oxides A Group III oxides A Group IV Hydroxides A Group IV oxides A Group IV nitrides A Any one or more of carbides of Group VIII elements or alkaline silicates of transition metal elements other than Group VIII; The total amount of the thermoplastic polymer, the thermal conductive filler compound and the viscosity reducer is 100 parts.
2. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 1, characterized in that: The first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler has a density less than 3 g / cm 3 Sheet insulation filler; The fourth thermally conductive filler has a density less than 4 g / cm 3 Granular insulating filler.
3. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 1 or 2, characterized in that: The first thermally conductive filler, the second thermally conductive filler or the third thermally conductive filler has a density less than 3 g / cm 3 Flake boron nitride (BN); The fourth thermally conductive filler has a density less than 4 g / cm 3 Granular alumina Al2O3.
4. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 1, characterized in that: The total weight of the insulating composite is 100 parts, and the sum of the weight parts of the thermoplastic polymer and the viscosity reducer is 35-60 parts; The ratio of the mass fraction of the thermoplastic polymer to the mass fraction of the viscosity reducer is not less than 2.5-3:
1.
5. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 1, characterized in that: The thermoplastic polymer is any one or more of a carbon-based linear polymer obtained by addition polymerization or copolymerization of olefin monomers through carbon-carbon double bonds (-C=C-), a carbon-based linear polymer whose main chain contains an amide bond obtained by stepwise polycondensation or ring-opening polymerization, a carbon-based linear polymer whose main chain contains an ester group obtained by stepwise polycondensation or ring-opening polymerization, or a carbon-based linear polymer whose main chain contains an urethane group, and a carbon-based linear polymer obtained by stepwise addition polymerization using diisocyanates and diols.
6. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 5, characterized in that: The carbon-based linear polymer obtained by addition polymerization or copolymerization of olefin monomers through carbon-carbon double bonds (-C=C-) is any one or more of polyethylene, polypropylene, polystyrene, polyvinyl chloride, polymethyl methacrylate, ethylene-propylene rubber, ethylene-vinyl acetate copolymer, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-ethyl acrylate copolymer, ethylene-propylene rubber, triblock copolymer with styrene and butadiene as monomers, acrylonitrile-butadiene-styrene block copolymer or butyl rubber.
7. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 5, characterized in that: The carbon-based linear polymer having an amide bond in the main chain obtained by stepwise polycondensation or ring-opening polymerization is any one or more of polyamide 6, polyamide 66, polyamide 610, polyamide 1010, and dimer acid-based polyamide.
8. A low-pressure injection-molded thermally conductive insulating composite as claimed in claim 5, characterized in that: The carbon-based linear polymer containing an ester group in the main chain obtained by stepwise polycondensation or ring-opening polymerization is any one or more of polyethylene terephthalate, polybutylene terephthalate, polyethylene isophthalate, polyethylene isophthalate, butylene adipate-butylene terephthalate copolymer, polyethylene furandicarboxylate, polybutylene furandicarboxylate, polylactic acid, and lactic acid-glycolic acid copolymer.
9. The low-pressure injection-molded thermally conductive insulating composite according to claim 1, characterized in that: The thermoplastic polymer is a dimer acid type polyamide, which is obtained from the following monomers by stepwise polycondensation or ring-opening polymerization: (1) Dimer acid with a molecular weight of 100-10000;. (2) diamines containing 2 to 20 carbon atoms in the main chain; (3) dibasic acids with a main chain containing 4 to 20 carbon atoms; (4) Polyetheramine with a molecular weight of 100-10000.
10. The low-pressure injection-molded thermally conductive insulating composite according to claim 1, characterized in that: The viscosity reducing agent is a carbon-based linear oligomer with a molecular weight not exceeding 2,000.
Citation Information
Patent Citations
Heat conduction type ethylene vinylacetate copolymer hot melt adhesive and preparation method thereof
CN101935503B
A thermally conductive hot melt adhesive and its preparation method
CN103555262B
High thermally conductive low pressure mouldable hotmelt
CN107667156A
A method for preparing a thermally conductive hot melt adhesive
CN109370479B
An electrically conductive, hot-melt adhesive or moulding composition
CN109416953A